Recovery Networks and Community Connections: Identifying Connection Needs and Community Linkage Opportunities in Early Recovery Populations. Issue 1 (2nd January 2017) - Best, David; Irving, Jamie; Collinson, Beth; Andersson, Catrin; Edwards, Michael
ABSTRACT: There is a consistent evidence base showing that recovery pathways are initiated and enhanced by positive social networks and the underlying changes in social identity that is associated with the transition from stigmatized and excluded groups to positive and prosocial groups. There is also a growing literature that focuses on community engagement as a vital ingredient of recovery journeys, with engagement in recreational activities, training and employment, volunteering, and mutual aid and other peer activities seen as important components of a Recovery-Oriented System of Care (ROSC). The mechanism for identifying such community assets that has been widely used is Asset-Based Community Development (ABCD), and the process for engaging people in such groups is known as Assertive Linkage. The current article introduces two innovative research methods—social identity mapping (SIM)—and Assertive Linkage and ABCD to create a model for identifying individuals in early recovery in need of community support and strong linkage approaches. The resulting "ice cream cone" model of assertive community connections provides a practical framework for implementing one aspect of generating a ROSC, building individual recovery capital through positive networks and building community assets, underpinned by the idea of recovery capital as a metric that can be quantified and used as the basis for recovery support and planning.